High‐Resolution Terrestrial Water Storage Anomalies and Components in China From GRACE/GFO via Joint Inversion Downscaling - Yuhao Xiong; Wei Feng; Hongbing Bai; Wei Chen; Zhongshan Jiang; Min Zhong (Water Resources Research, 2025)
Abstract Satellite gravimetry (Gravity Recovery and Climate Experiment (GRACE)/GRACE Follow‐On (GFO)) has solved the challenge of monitoring global and basin‐scale terrestrial water storage anomalies (TWSA) at monthly intervals and spatial scales of ∼330 km. However, this spatial resolution limits its ability to capture small‐scale basin water variations, and GRACE/GFO cannot independently distinguish different vertical water components, which further restricts its application in hydrological studies. To address these challenges, we propose a joint inversion downscaling method that combines hydrological simulations and GRACE/GFO observations. Our approach effectively inherits the high spatial resolution patterns from hydrological models and preserves the large‐scale accuracy from the GRACE/GFO measurements. It also allows for the flexible inclusion of mascon groups, reducing dependence on hydrological models and improving the performance in glacier regions, where traditional downscaling methods struggle. We reconstructed high‐resolution (i.e., 0.5°) TWSA and its components in China, for example, groundwater and glacier, revealing their finer spatial trends and localized water mass changes. From 2002 to 2022, our study details TWSA and flux changes in different China's basins, demonstrating marked regional disparities. Groundwater depletion rate in the North China Plain is 2.43 ± 0.18 cm/yr, equivalent to 3.35 ± 0.25 Gt/yr, and glacier mass loss rate in the High Mountain Asia (HMA) is 34.10 ± 1.55 Gt/yr. We also map the spatiotemporal patterns of glaciers in HMA and surface water changes in the endorheic Tibetan Plateau. This work has successfully extracted high‐resolution signals for different vertical water components in China, providing valuable insights for regional water resource management and disaster mitigation.